2009
DOI: 10.1359/jbmr.081107
|View full text |Cite
|
Sign up to set email alerts
|

JNK Activity Is Essential for Atf4 Expression and Late-Stage Osteoblast Differentiation

Abstract: Osteoblasts differentiate from mesodermal progenitors and play a pivotal role in bone formation and mineralization. Several transcription factors including runt-related transcription factor 2 (RUNX2), Osterix (OSX), and activating transcription factor4 (ATF4) are known to be crucial for the process, whereas the upstream signal transduction controlling the osteoblast differentiation sequence is largely unknown. Here, we explored the role of c-jun N-terminal kinase (JNK) in osteoblast differentiation using in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
125
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 40 publications
14
125
0
1
Order By: Relevance
“…(43) Moreover, blocking JNK activity has previously been found to upregulate BMP2-induced ALP activity and osteopontin (OPN) expression. (13,39) Taken together, these data support our conclusion that JNK1 functions as a negative regulator in BMP2-induced osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…(43) Moreover, blocking JNK activity has previously been found to upregulate BMP2-induced ALP activity and osteopontin (OPN) expression. (13,39) Taken together, these data support our conclusion that JNK1 functions as a negative regulator in BMP2-induced osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, Matsuguchi et al reported that JNK2 activation by osteogenic supplements is essential for ATF4 expression and late-stage differentiation in pre-osteoblast cells. (39) Liu et al reported that activation of JNK1, but not JNK2, increases cellular responsiveness to BMP2 by increasing the phosphorylation of Smad1 and association of Smad1 with BMP type I receptor. (27) However, the activity of Smad1 regulated by phosphorylation depends on the phosphorylation region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(22) JNK has been reported to be required for late-stage differentiation of preosteoblasts and BMP-2-induced differentiation of preosteoblasts and pleuripotent cells. (18,20,23,24) JNK is considered a critical regulator of activating transcription factor 4, osteocalcin, and bone sialoprotein expression in spontaneously differentiating osteoblasts. (21,23) These studies suggest that JNK plays an important role in the induction of osteogenesis by BMP-2.…”
Section: Introductionmentioning
confidence: 99%
“…(18,20,23,24) JNK is considered a critical regulator of activating transcription factor 4, osteocalcin, and bone sialoprotein expression in spontaneously differentiating osteoblasts. (21,23) These studies suggest that JNK plays an important role in the induction of osteogenesis by BMP-2. However, the exact mechanism of this interaction is still unclear.…”
Section: Introductionmentioning
confidence: 99%